Employee retention in the manufacturing sector: is there a simple solution? - Subramaniam, Chandrakantan; Suan, Choo Ling; Johari, Johanim (Springer, 2019)
Employee retention is one of the key issues in many organizations. The inability to retain employees can cost the organization financially and nonfinancially. Although employee retention has been widely investigated, less attention is given to the manufacturing sector. Such neglect is unfortunate because the manufacturing sector in Malaysia is reported to experience between 18% and 20% annual human capital turnover rates. This chapter argues that despite having limited resources to formulate a holistic mechanism to retain employees, concern for employee retention should not be ignored. Against this backdrop, this chapter proposes a model that hypothesizes the role of management practices in promoting employee retention initiatives.